Dioscin suppresses TGF-β1-induced epithelial-mesenchymal transition and suppresses A549 lung cancer migration and invasion. Issue 15 (1st August 2017) - Lim, Won-Chul; Kim, Hyunhee; Kim, Young-Joo; Choi, Kyung-Chul; Lee, In Ho; Lee, Ki Heon; Kim, Mi Kyung; Ko, Hyeonseok
Graphical abstract: Abstract: Epithelial-to-mesenchymal transition (EMT), an important cellular process, occurs during cancer development and progression, has a crucial role in metastasis by enhancing the motility of tumor cells. Dioscin is a polyphenolic component isolated from Phyllanthus amarus, which exhibits a wide range of pharmacological and physiological activities, such as anti-tumor, anti-inflammatory, anti-obesity, anti-fungal, and anti-viral activities. However, the possible role of dioscin in the EMT is unclear. We investigated the suppressive effect of dioscin on the EMT. Transforming growth factor-beta 1 (TGF-β1) is known to induce EMT in a number of cancer cell types and promote lung adenocarcinoma migration and invasion. To verify the inhibitory role of dioscin in lung cancer migration and invasion, we investigated the use of dioscin as inhibitors of TGF-β1-induced EMT in A549 lung cancer cells in vitro . Here, we found that dioscin prominently increased expression of the epithelial marker E-cadherin and expression of the mesenchymal marker N-cadherin and Snail during the TGF-β1-induced EMT. In addition, dioscin inhibited the TGF-β1-induced increase in cell migration and invasion of A549 lung cancer cells. Also, dioscin remarkably inhibited TGF-β1-regulated activation of MMP-2/9, Smad2, and p38. Taken together, our findings provide new evidence that dioscin suppresses lung cancer migration, and invasion in vitro by inhibiting the TGF-β1-induced EMT.